Effect of aqueous extract of Capparis spinosa, Azadirachta indica, and Myrtus communis leaves in the viability of Echinococcus granulosus protoscoleces of human and sheep origin in vitro - Ibrahim Abdullah; Arqam Azhar (College of Education for Pure Sciences, 1999)
ABSTRACT Results of the present study revealed significant inhibitory effect of aqueous extracts of the fruits of capparis spinosa, Melia azadrach and the leaves of Myrtus communis at concentrations 50, 100, 200, and 300 mg/ml for each of these plants on the viability of the protoscoleces of Echinococcus granulosus of human and sheep origin in vitro.The concentration of 300 mg/ml and sometimes the concentration 200 mg/ml of these plants causes the death of all protoscoleces in 45 and 60 minutes.